Intention and Concerns about HPV Vaccination among In-School Adolescents in Ibadan, Oyo State, Nigeria (2023)
Background: Human papillomavirus (HPV) is a very common sexually transmitted infection responsible for some cancers including cervical cancer. Despite nearly half of the Nigerian population being at risk (women <25), vaccination uptake against the infection is still less than 5%. Methodology: This cross-sectional descriptive survey was conducted using a multi-stage sampling technique. A semi-structured questionnaire was administered to 300 in-school adolescents aged 15-19 years, across 15 private and public secondary schools in Ibadan-North and Ibadan North-West of Oyo State, whose parents gave consent. The data was analysed using descriptive and inferential statistics in SPSS v21. Cronbach’s alpha coefficient was used to measure internal consistency reliability while categorical tables were compared using chi-square and regression analysis with a p-value <0.05. Results: The mean age of respondents was 15.8 ± 0.84 years. Half of them were females (52.3%) and also attended private schools (56.3%). Very few of the respondents had heard about HPV (21.0%) and HPV vaccine (12.7%), however, more than half had heard about cervical cancer (55.3%). Few respondents had good knowledge (11.0%) and positive perception (27.0%) of HPV, cervical cancer and HPV vaccine. The major source of information was social media (46.2%). Half of the respondents reported intention to take the vaccine if recommended by their family doctor (56.3%) and if given parental approval (52.0%), however, many (60.7%) were concerned about the vaccine’s side effects.Conclusion: Findings show that parents and health workers influence adolescents’ HPV vaccination uptake.The study thus recommends the prioritization of parental involvement in HPV vaccination. Parents and health workers should therefore be targeted as key stakeholders in driving the awareness of HPV and uptake of HPV vaccine among adolescents.